Extracellular ATP Shapes a Defense-Related Transcriptome Both Independently and along with Other Defense Signaling Pathways. Issue 3 (10th January 2019) - Jewell, Jeremy B.; Sowders, Joel M.; He, Ruifeng; Willis, Mark A.; Gang, David R.; Tanaka, Kiwamu
Abstract : Extracellular ATP-responsive transcription interacts with other defense signaling pathways and relies on MYC and CAMTA transcription factors. Abstract: ATP is not only an essential metabolite of cellular biochemistry but also acts as a signal in the extracellular milieu. In plants, extracellular ATP is monitored by the purinergic receptor P2K1. Recent studies have revealed that extracellular ATP acts as a damage-associated molecular pattern in plants, and its signaling through P2K1 is important for mounting an effective defense response against various pathogenic microorganisms. Biotrophic and necrotrophic pathogens attack plants using different strategies, to which plants respond accordingly with salicylate-based or jasmonate/ethylene-based defensive signaling, respectively. Interestingly, defense mediated by P2K1 is effective against pathogens of both lifestyles, raising the question of the level of interplay between extracellular ATP signaling and that of jasmonate, ethylene, and salicylate. To address this issue, we analyzed ATP-induced transcriptomes in wild-type Arabidopsis ( Arabidopsis thaliana ) seedlings and mutant seedlings defective in essential components in the signaling pathways of jasmonate, ethylene, and salicylate (classic defense hormones) as well as a mutant and an overexpression line of the P2K1 receptor. We found that P2K1 function is crucial for faithful ATP-induced transcriptional changes and that a subset of genes is more responsive in the P2K1 overexpression line. We also found that more than half of the ATP-responsive genes required signaling by one or more of the pathways for the classical defense hormones, with the jasmonate-based signaling being more critical than others. By contrast, the other ATP-responsive genes were unaffected by deficiencies in signaling for any of the classical defense hormones. These ATP-responsive genes were highly enriched for defense-related Gene Ontology terms. We further tested the ATP-induced genes in knockout mutants of transcription factors, demonstrating that MYCs acting downstream of the jasmonate receptor complex and calmodulin-binding transcription activators are nuclear transducers of P2K1-mediated extracellular ATP signaling.